2020
DOI: 10.3390/app10186517
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability and Regulation before and after High Tibial Osteotomy and Rehabilitation

Abstract: Knee osteoarthrosis (OA) is a widespread orthopedic problem and a high tibial osteotomy (HTO) is a common treatment to minimize degeneration of the affected compartment. The primary aim of this study was to evaluate the postural regulation and stability among patients who underwent HTO and rehabilitation. This prospective study included 32 patients (55.3 ± 5.57 years) diagnosed with medial tibiofemoral OA. Each subject completed postural regulation and stability testing (Interactive Balance System), as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…It is possible that, in LOPD patients, additional effects on the muscle spindles [33] or spinal cord [34] [12,13]. In support of Brehme et al [13] and in contrast to Bartels et al [12], we showed hyperactivity of the somatosensory system in the presence of PN. This hyperactivity could also be observed in the cerebellar system (four patients had abnormal posturographic findings; Table 4).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It is possible that, in LOPD patients, additional effects on the muscle spindles [33] or spinal cord [34] [12,13]. In support of Brehme et al [13] and in contrast to Bartels et al [12], we showed hyperactivity of the somatosensory system in the presence of PN. This hyperactivity could also be observed in the cerebellar system (four patients had abnormal posturographic findings; Table 4).…”
Section: Discussionsupporting
confidence: 80%
“…However, no differences in sway between LOPD patients with or without PN were observed in F5-6 (averaged over all test positions), which has been shown to be affected in patients with diabetic polyneuropathy [23]. It is possible that, in LOPD patients, additional effects on the muscle spindles [33] or spinal cord [34] [12,13]. In support of Brehme et al [13] and in contrast to Bartels et al [12], we showed hyperactivity of the somatosensory system in the presence of PN.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…All tasks were conducted with the subjects head in a neutral alignment (vestibular). Detailed information about the calculated parameters and used test positions can be found in previous research [14][15][16][17]. All measurements were conducted at the same time of day and in a quiet room without any distractions.…”
Section: Study Design and Methodologymentioning
confidence: 99%
“…So far, there are only a few studies that deal with the postoperative effects of HTO surgery on postural control [ 5 , 6 ]. Hunt et al [ 5 ] observed 1 year postoperatively that single-leg steadiness in patients with knee osteoarthritis is not significantly different from that prior to HTO surgery.…”
Section: Introductionmentioning
confidence: 99%